2021
DOI: 10.1097/md.0000000000024938
|View full text |Cite
|
Sign up to set email alerts
|

The effect of probiotics on functional constipation in adults

Abstract: Background : Evacuation disorders are common in industrialized countries, affecting an average of 15% to 20% of the healthy adult population. Probiotic therapy can reduce functional constipation and increase both the number of weekly bowel movements and quality of stools. Based on the hypothesis that a combination of more strains may provide better results for constipation and facilitate adherence to treatment, this study will evaluate the efficacy and safety of a combination of different strains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Several studies have shown that probiotics may be effective in treating constipation [8]. In our study, a probiotic mixture, BIO-THREE , including Streptococcus faecalis , Bacillus mesentericus , and Clostridium butyricum , significantly relieved constipation and improved insulin resistance among patients with schizophrenia [9].…”
Section: Probiotics Improved Both Constipation and Insulin Resistance In Schizophrenic Patientsmentioning
confidence: 54%
“…Several studies have shown that probiotics may be effective in treating constipation [8]. In our study, a probiotic mixture, BIO-THREE , including Streptococcus faecalis , Bacillus mesentericus , and Clostridium butyricum , significantly relieved constipation and improved insulin resistance among patients with schizophrenia [9].…”
Section: Probiotics Improved Both Constipation and Insulin Resistance In Schizophrenic Patientsmentioning
confidence: 54%
“…Water consumption rates on the day of defecation were also recorded. Faecal transit times were based on the BSS: scores of 1-2 indicate slow transit, 3-5 indicate normal transit, and 6-7 indicate fast transit times (Lewis and Heaton, 1997;Mitelmão et al, 2021).…”
Section: Assessment Of Lower Gi-related Events Using Bowel Habit Diariesmentioning
confidence: 99%
“…In medical practice, probiotics are often used to treat functional diseases of the gastrointestinal tract, beneficially altering the gut microbiota and relieving abdominal symptoms, including constipation [ 51 , 52 , 53 ]. Probiotics may improve intestinal transit time, stool consistency, and frequency [ 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%